Pyrenophora tritici–repentis in Tunisia: Race Structure and Effector Genes - Kamel, Sana; Cherif, Mejda; Hafez, Mohamed; Despins, Therese; Aboukhaddour, Reem (Frontiers in Plant Science, 2019)
Tan spot is a destructive foliar wheat disease worldwide and caused by the ascomycete fungus Pyrenophora tritici–repentis (Ptr); it has become more frequent in Tunisia over the last decade. In this study, the virulence of 73 single-spore isolates, collected from durum and bread wheat fields during 2017–2018 growing season, was evaluated on four differential wheat genotypes. This was followed by polymerase chain reaction tests with specific primers for the effector genes ToxA, ToxB, and toxb (ToxB-homolog). Sequence analysis to validate the identity of the amplified genes was followed, and ToxA amplicons from a subset of 22 isolates were analyzed to determine its haplotype identity. Ptr isolates from Tunisia were grouped in races 2, 4, 5, and 7, and 44% of the tested isolates did not fit under any known race, and were denoted here as atypical. These atypical isolates induced the same symptoms as race 7 isolates, extensive necrosis, and chlorosis on susceptible genotypes, but lacked the ToxA gene. ToxA is the only identified necrosis-inducing effector in Ptr, and was amplified in 51% of tested isolates, and shared identical sequence to previously identified haplotype (H15). ToxB and its homolog toxb were present in 97% and 93% of tested isolates, respectively. Ptr in Tunisia lacked Ptr ToxC activity, and none of the tested isolates induced the specific symptoms of that effector. Race 7 and the atypical isolates dominated the Tunisian Ptr population, while races 2, 4, and 5 were found at low percentages. In conclusion, ToxB and its homolog were the most dominant genes in Ptr from Tunisia, and the majority of the isolates induced necrosis and chlorosis on Ptr ToxA and Ptr ToxB susceptible wheat genotypes. However, only about half of that necrosis can be attributed to ToxA presence, this result necessitates further research to investigate the prevalence of additional necrotic effector(s). Terminology: in this paper, Pyrenophora tritici–repentis abbreviated as Ptr, the effectors are referred to by Ptr ToxA, Ptr ToxB and Ptr ToxC, and the genes coding for them are written in italic as ToxA, ToxB, and ToxC, respectively.